Differences between native and immigrant women in Taiwan in factors associated with caesarean section: A prospective observational study. Issue 10 (26th November 2017) - Weng, Shiue-Shan; Lin, Chen-Li; Tai, Chen-Jei; Chien, Li-Yin
ABSTRACT: This study aimed to examine the association of social support, social factors, and maternal complications with caesarean deliveries in native and immigrant women, and to explore the association between acculturation and caesarean deliveries in immigrant women in Taiwan. This prospective panel study was conducted from August 2012 through April 2014 and included 222 native and 147 immigrant pregnant women in Taiwan. Caesarean rates did not differ significantly between native and immigrant women, including the overall caesarean rate (28.8%, 32.0%), medically indicated caesarean (22.5%, 24.5%), and caesarean without medical indications (6.3%, 7.5%). Results of multiple logistic regression models revealed that maternal complications and household activity support were positively associated with caesarean deliveries. Both native and immigrant women with high levels of informational support were less likely to receive caesareans. Immigrant women who were older than 35 years, had a middle level socioeconomic status, and perceived a high level of acceptance of caesarean in Taiwan were more likely to have caesarean deliveries. Informational support was a protective factor for caesarean delivery, whereas household activity support offered by the family was positively associated with caesarean delivery. Perceived acceptance level in mainstream society could affect immigrant women's use of caesarean delivery.